Saliva Neurofilament Light Chain Is Not a Diagnostic Biomarker for Neurodegeneration in a Mixed Memory Clinic Population - Gleerup, Helena Sophia; Sanna, Federica; Høgh, Peter; Simrén, Joel; Blennow, Kaj; Zetterberg, Henrik; Hasselbalch, Steen Gregers; Ashton, Nicholas J.; Simonsen, Anja Hviid (Frontiers in Aging Neuroscience, 2021)
Neurodegenerative disorders are an increasing concern, and consequently non-invasive biomarkers are needed. Neurodegeneration leads to an increasing release of the neuron-specific neurofilament light chain (NfL) protein into body fluids, including cerebrospinal fluid (CSF) and blood. Numerous studies have shown that NfL levels in CSF and blood can monitor neurodegeneration. Saliva has been suggested to be a candidate biofluid for the measurement of biomarkers for Alzheimer’s disease (AD). In this study, salivary NfL was for the first time measured and compared to plasma NfL in consecutive a cohort of patients referred to cognitive assessments. From two mixed, memory clinic cohorts, 152 consecutive patients and 17 healthy controls were recruited. Of these, 135 also had a matching plasma sample. All saliva and plasma samples were analyzed for NfL, and the association between saliva and plasma NfL, and CSF levels of total tau (t-tau), phosphorylated tau (p-tau), and beta amyloid 1-42 (A42) were investigated. In total, 162/169 had quantifiable levels of salivary NfL by single molecule array (Simoa). No statistically significant differences were found in salivary NfL concentration across the diagnostic groups, but as expected, significant increases were found for plasma NfL in dementia cases (P=<0.0001). There was no association between saliva and plasma NfL levels. Furthermore, saliva NfL did not correlate with CSF A42, p-tau or tau concentrations. Although NfL in saliva was quantifiable, it did not correlate with plasma NfL and was not useful to detect AD or other dementias. Saliva NfL concentration does not reflect neurodegeneration in the brain.